Pengaruh Role Model’s Influence pada Materialism dan Marketplace Knowledge Periode Remaja Akhir - Rita Rita (Binus Business Review, 2013)
The aim of the study is to examine the positive influence of direct role model's influence (father, mother, and peer) and vicarious role model’s influence (celebrities and athletes) with materialism and marketplace knowledge late adolescents periodic. The subjects of this research are respondents late adolescents periodic inscribed as student college in Jakarta. There are 281 respondents are recorded. Purposive is taken as sampling technique. The hypotheses are analyzed with regression analysis with SPSS 11.5 software. The finding shows that, there is not significant difference between direct role model's influence (father, mother, and peer) to materialism and marketplace knowledge what is experienced by late adolescents. But there is significant difference between vicarious role model’s influence (celebrities and athletes) to materialism and marketplace knowledge what is experienced by late adolescents.